ChAdOx1 nCoV-19 (AZD1222) protects Syrian hamsters against SARS-CoV-2 B.1.351 and B.1.1.7 - Robert J. Fischer; Neeltje van Doremalen; Danielle R. Adney; Claude Kwe Yinda; Julia R. Port; Myndi G. Holbrook; Jonathan E. Schulz; Brandi N. Williamson; Tina Thomas; Kent Barbian; Sarah L. Anzick; Stacy Ricklefs; et al. (Nature Communications, 2021)
Emerging SARS-CoV-2 variants raise concerns about vaccine effectiveness. Here, the authors show that the ChAdOx1 nCoV-19 (AZD1222) vaccine protects Syrian hamsters from pulmonary infection and disease after infection with SARS-CoV-2 B.1.351 or B.1.1.7 variants.